Analyzing the Impact of Mergers on the Islamic Performance Index: A Comparative Study of State-Owned Islamic Commercial Banks in Indonesia - Juniarti, Dini; Suhendar, S.; Etika , Citra (Manunggal Halim Jaya, 2025)
The merger between BRI Syariah, BNI Syariah, and Bank Syariah Mandiri into Bank Syariah Indonesia (BSI) in 2021 is expected to increase competitiveness and strengthen the role of Islamic banking in Indonesia. This study aims to analyze the impact of mergers on the performance of BUMN Islamic Commercial Banks using the Islamicity Performance Index (IPI) approach. This study uses a comparative quantitative approach with secondary data in the form of financial statements for 2017-2024. The data were collected and processed using Microsoft Excel 2010 and EViews 12. The IPI indicators used include Zakat Performance Ratio (ZPR), Profit Sharing Ratio (PSR), Equitable Distribution Ratio (EDR), and Islamic Income vs Non-Islamic Income Ratio (IIcR). The analysis results show that three out of four indicators, namely ZPR, PSR, and IIcR, experienced statistically significant changes after the merger, reflecting improvements in zakat management, profit sharing effectiveness, and compliance with Islamic income principles. However, the EDR indicator did not show any significant difference, indicating that the equitable aspect of wealth distribution has not been optimized. The findings suggest that the merger positively impacts most aspects of Islamic financial performance. The implications of this study emphasize the importance of strengthening socio-economic strategies in post-merger policies so that the function of Islamic financial institutions as agents of justice and welfare can be achieved as a whole according to the principles of Sharia Enterprise Theory.